Inside Front Cover: Consideration for the scale‐up manufacture of nanotherapeutics—A critical step for technology transfer (View 5/2021). Issue 5 (27th October 2021) - Liu, Xiangsheng; Meng, Huan
Abstract : Chemistry, manufacturing and controls of nanotherapeutics ( nano ‐CMC) is a critical step for translational nanomedicine. Establishment of reproducible, scalable, transferrable and controllable nano manufacture process is a major barrier that needs to be overcome in terms of moving various nanotherapeutics from bench to bed. The image of article number 20200190, Xiangsheng Liu and Huan Meng illustrate the process of developing nanotherapeutics from the laboratory investigation, preclinical validation in animal studies to scale up manufacture and clinical translation.